Central antagonism of orexin type-1 receptors attenuates the development of morphine dependence in rat locus coeruleus neurons. (5th November 2017) - Fakhari, Mojgan; Azizi, Hossein; Semnanian, Saeed
Highlights: Firing rate of LC neurons increased following naloxone injection in morphine-dependent rats. OX1R blockade prevented naloxone-induced neuronal excitation in LC neurons. Naloxone injection increased the cAMP level in LC neurons of morphine-dependent rats. OX1R blockade prevented naloxone-induced increase in cAMP level. OX1R are involved in the development of morphine dependence in LC neurons. Abstract: Prolonged use/abuse of opioid agonists leads to development of severe dependence to these drugs. Orexin-A has a crucial role in development of morphine dependence. The locus coeruleus (LC) is implicated in the expression of morphine withdrawal signs. Hyperactivity of LC neurons as well as increased intracellular cyclic adenosine monophosphate (cAMP) level temporally corresponds to the expression of opioid withdrawal behaviors. In this study the effect of central OX1R blockade on neuronal activity and cAMP content of LC neurons was investigated following naloxone administration in morphine-dependent rats. Male Wistar rats weighing 250–300 g were used in this study. To induce morphine dependence, morphine was injected intraperitoneally (10 mg/kg, i.p.) once a day for seven consecutive days. A selective OX1R antagonist (SB-334867) was microinjected into the cerebral ventricle (10 µg/10 µl) immediately before each morphine injection. The activity of LC neurons was investigated using in vivo extracellular single-unit recording on day 8 and naloxone (2 mg/kg, i.p.) was administered after 10-min baseline recording. In addition, immunohistofluorescence method was used to measure the effect of naloxone on coerulear cAMP level. Chronic morphine injection induced morphine dependence in LC neurons which was revealed as a significant increase in LC neuronal firing rate in response to naloxone. The results of this study indicated that SB-334867 administration prior to each morphine injection prevents naloxone-elicited neuronal activation within the LC. In addition, naloxone injection enhanced the cAMP concentration in LC neurons of morphine-dependent animals and this effect was significantly reduced by OX1R blockade.